Carboxamide substituted tetramethylcyclopentadiene - synthesis, characterisation and its iridium(iii) complex catalysed reduction of imines - Mwansa, Joseph M; Stirling, Matthew J; Sweeney, Gemma; Hanusek, Jiří; Váňa, Jiří; Page, Michael, I (Royal Society of Chemistry, 2022)
The novel dimeric iodo-iridium(iii) complex, [Ir(Cp*CONMe2)I-2](2), (Cp*CONMe2 = eta(5)-N,N-2,3,4,5-hexamethylcyclopenta-2,4-diene carboxamide) bearing an amide moiety within the tetramethylcyclopentadiene ring, has been synthesised and characterised. The ligand Cp*CONMe2 is synthesised as two regioisomers, however the 2-substituted isomer exists as two distinguishable conformers due to restricted rotation about the amide carbonyl carbon and the ring carbon. The relative acidities of Cp*CONMe2 and Cp* are compared by their relative rates of H/D exchange. The iridium complex of N,N-2,3,4,5-hexamethylcyclopenta-2-4-diene carboxamide [IrCp*CONMe2] and (R,R)-1,2-diphenyl-N '-tosylethane-1,2-diamine ((R,R)-TsDPEN) has been evaluated in the transfer hydrogenation of imines under acidic conditions - a 5 : 2 molar ratio of formic acid : triethylamine as the hydride source for the transfer hydrogenation of 1-methyl-3,4-dihydroisoquinoline (DHIQ) and its 6,7-dimethoxy derivative in acetonitrile. A decreasing enantiomeric excess with reaction progress is attributed to different kinetic orders for formation of the two product amine enantiomers. The pseudo zero-order formation of the R-amine may be due to a pre-steady-state formation of the less stable form of the diastereomeric catalyst. By contrast, both enantiomeric amines from 1-fluorinated methyl DHIQs as substrates for reduction are formed by pseudo first-order processes.
Karboxamidem substituovaný tetramethylcyklopentadien - syntéza, charakterizace a jeho iridium(iii) komplexem katalyzovaná redukce iminů
Keywords: kinetics; hydrogenation; mechanism; carboxamide; irridium complex; kinetika; hydrogenace; mechanismus; karboxamid; komplex iridia